Commercially available angiotensin II At₂ receptor antibodies are nonspecific. - Roman Hafko; Sonia Villapol; Regina Nostramo; Aviva Symes; Esther L Sabban; Tadashi Inagami; Juan M Saavedra (PLoS ONE)
Commercially available angiotensin II At₂ receptor antibodies are widely employed for receptor localization and quantification, but they have not been adequately validated. In this study, we characterized three commercially available At₂ receptor antibodies: 2818-1 from Epitomics, sc-9040 from Santa Cruz Biotechnology, Inc., and AAR-012 from Alomone Labs. Using western blot analysis the immunostaining patterns observed were different for every antibody tested, and in most cases consisted of multiple immunoreactive bands. Identical immunoreactive patterns were present in wild-type and At₂ receptor knockout mice not expressing the target protein. In the mouse brain, immunocytochemical studies revealed very different cellular immunoreactivity for each antibody tested. While the 2818-1 antibody reacted only with endothelial cells in small parenchymal arteries, the sc-9040 antibody reacted only with ependymal cells lining the cerebral ventricles, and the AAR-012 antibody reacted only with multiple neuronal cell bodies in the cerebral cortex. Moreover, the immunoreactivities were identical in brain tissue from wild-type or At₂ receptor knockout mice. Furthermore, in both mice and rat tissue extracts, there was no correlation between the observed immunoreactivity and the presence or absence of At₂ receptor binding or gene expression. We conclude that none of these commercially available At₂ receptor antibodies tested met the criteria for specificity. In the absence of full antibody characterization, competitive radioligand binding and determination of mRNA expression remain the only reliable approaches to study At₂ receptor expression.